PERSEPSI MASYARAKAT TERHADAP KEARIFAN LOKAL DALAM PENGELOLAAN MATA AIR TUBAKI DI KAWASAN HUTAN SUAKA MARGASATWA KATERI (Studi Kasus Desa Kamanasa, Kecamatan Malaka Tengah, Kabupaten Malaka) - Maria Heltiana Amaral; Ludji Michael Riwu Kaho; Wilhelmina Seran (Wana Lestari, 2020)
Tubaki spring is one of the springs in Kateri Wildlife Sanctuary area. This study aims to determine people's perceptions of the local wisdom of Tubaki Springs in Kamanasa Village, Malaka Regency and this research was conducted in Kamanasa Village, Central Malaka Sub-District, Malaka District using qualitative methods carried out from July - October 2019. Data collected in the form of primary and secondary data. This primary data obtained the characteristics of respondents and data regarding public knowledge while secondary data obtained from the literature study from several related agencies and related institutions in the study area. The results showed that 1). The village of Kamanasa perceives the nature of Tubaki Springs positively, the Tubaki spring is seen as a gift from God that strongly supports the livelihoods of residents. 2) The people of Kamanasa Village have local wisdom in the form of: a) knowledge, including knowledge of titen., B). Values, c) Ethics and morals. d) norms consisting of recommendations, prohibitions and sanctions, and expressions. Local wisdom is used and applied as a guide for attitudes and behavior in preserving springs, in various physical and ritual activities, routine and incidental. On the basis of benefits, the community's enthusiasm for maintaining and preserving their traditions. To preserve the discharge of the Tubaki spring, not only by preserving existing traditions, but good forest management is needed around the spring and its upper areas.